2012
DOI: 10.1186/1472-6831-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Screening and detection of human papillomavirus (HPV) high-risk strains HPV16 and HPV18 in saliva samples from subjects under 18 years old in Nevada: a pilot study

Abstract: BackgroundHuman papillomaviruses (HPV) are oncogenic and mainly associated with cervical cancers. Recent evidence has demonstrated HPV infection in other tissues, including oral epithelia and mucosa. Although a recent pilot study provided new information about oral HPV status in healthy adults from Nevada, no information was obtained about oral HPV prevalence among children or teenagers, therefore, the goal of this study is to provide more detailed information about oral prevalence of high-risk HPV among child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 76 publications
3
22
0
Order By: Relevance
“…A range of potential risk factors for oral HPV-16 infections, such as close contact with HPV-positive parents during early childhood [12], or maternal cervical/vaginal contact with a HPV-positive mother during birth [36] have been proposed. In addition, it is widely accepted that oral sexual activities are an established risk factor for HPV-16 infection [15,25,26,27,28,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of potential risk factors for oral HPV-16 infections, such as close contact with HPV-positive parents during early childhood [12], or maternal cervical/vaginal contact with a HPV-positive mother during birth [36] have been proposed. In addition, it is widely accepted that oral sexual activities are an established risk factor for HPV-16 infection [15,25,26,27,28,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 genotypes of mucosotropic HPV have been identified with low-risk types (most common 6, 11) being associated with benign lesions and high-risk types (most common 16, 18) being associated with malignant conditions (such as cervical malignancy and OPC) [11,12,13]. HPV-16-driven OPC constitute 90% of HPV-positive OPC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the HPV insertion loci are randomly or regularly distributed in human genome has been widely discussed but remains unclear [11,15,23,31,37]. Theoretically, highly successful integration should lead to persistent expression of viral proteins that is sufficiently robust to induce malignancy.…”
Section: Introductionmentioning
confidence: 98%
“…Mantet al even suggested that HPV infection could be acquired from peers by horizontal transmission [11]. Recently there is more evidence of oral HPV transmission in children and adolescents through close personal contact anywhere from shared toys and eating utensils to kissing and bathing [10]. In our case, indirect transmission via fomites is likely with possible direct autoinoculation to multiple sites in the mouth following oral trauma or biting.…”
Section: Discussionmentioning
confidence: 76%
“…More recent literature suggests the possibility of oral HPV infection as a result of direct personal contact between family members or indirect contact (fomite transmission) [9,10]. Mantet al even suggested that HPV infection could be acquired from peers by horizontal transmission [11].…”
Section: Discussionmentioning
confidence: 99%